Citizenship in Australia : a guide to Commonwealth Government records / David Dutton. - Dutton, David. (Research guide (National Archives of Australia), 1999)
Contains a detailed summary of records pertaining to citizenship and naturalization held by the National Archives of Australia. Includes addresses etc. of each state's repository branch of the National Archives.